Case Report: IL-6 suppression: a potential strategy for mitigating severe immune-related adverse events in nivolumab and ipilimumab therapy for malignant pleural mesothelioma - Yanagisawa, Asako; Fukaya, Takumi; Noda, Kento; Kojima, Hiroshi; Shimizu, Hidefumi (Frontiers in Oncology, 2025)
BackgroundMalignant pleural mesothelioma (MPM) is a rare and aggressive cancer with a poor prognosis, often presenting challenges in treatment. The CheckMate-743 trial demonstrated significant improvements in overall survival with the combination therapy of nivolumab and ipilimumab in advanced MPM. However, the management of immune-related adverse events (irAEs) remains a critical concern.Case presentationWe present a 74-year-old male with a history of polymyalgia rheumatica (PMR), diagnosed two years prior. His PMR was initially treated with corticosteroids, but tapering the dose was difficult. Therefore, tocilizumab was initiated one year before the current presentation, leading to a stable remission. One month before starting cancer therapy, tocilizumab was discontinued while the patient’s PMR remained well-controlled. He then developed multiple serious irAEs following the first cycle of nivolumab and ipilimumab for advanced MPM. These included cytokine release syndrome (CRS), immune-related aseptic meningitis, and liver dysfunction. All irAEs were successfully managed with corticosteroids, and the patient’s tumor progression remained under control.ConclusionThis case suggests that residual IL-6 suppression from prior tocilizumab therapy may attenuate the severity of subsequent irAEs, permitting effective management without compromising anti-tumor efficacy. IL-6 modulation could be a promising strategy to improve the therapeutic index of dual checkpoint inhibition in MPM.